2021
DOI: 10.3390/antibiotics10040463
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Screening of Essential Oils as Substances Which Enhance Antibiotic Activity Using a Modified Well Diffusion Method

Abstract: Antimicrobial resistance is recognized as one of the major global health challenges of the 21st century. Synergistic combinations for antimicrobial therapies can be a good strategy for the treatment of multidrug resistant infections. We examined the ability of a group of 29 plant essential oils as substances which enhance the antibiotic activity. We used a modified well diffusion method to establish a high-throughput screening method for easy and rapid identification of high-level enhancement combinations agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Cui et al (2021) revealed that 25 essential oils possessed antibacterial activity against MRSA. Orange and petitgrain essential oils showed significant synergistic effects with amikacin against Salmonella typhimurium and Klebsiella pneumoniae .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cui et al (2021) revealed that 25 essential oils possessed antibacterial activity against MRSA. Orange and petitgrain essential oils showed significant synergistic effects with amikacin against Salmonella typhimurium and Klebsiella pneumoniae .…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding values for NPG and penicillin were 1.98-log 10 CFU ml À1 and 2.09-log 10 CFU ml À1 , respectively. As described in the literature (Cui et al, 2021;G omara & Ram on-García, 2019), a synergistic antibacterial effect is a ≥ 2-log 10 CFU ml À1 reduction compared with the most active individual drug. For ATCC 43300, the combination of TPG and penicillin showed a strong synergistic effect, with a decrease of 5.21 log 10 CFU ml À1 (TPG) to 7.13 log 10 CFU ml À1 (penicillin) (Figure 3).…”
Section: Time-kill Assaysmentioning
confidence: 94%
See 1 more Smart Citation
“…The antibacterial potential of synthesized Chi/AuNPs was determined by agar well diffusion assay against the tested selected bacterial strains [ 46 ]. All bacteria examined had a density of 0.5 McFarland at turbidity.…”
Section: Methodsmentioning
confidence: 99%
“…According to, Clinical & Laboratory Standards Institute (CLSI) guidelines (Cui et al, 2021) muller Hinton agar plates were inoculated with the tested organisms using a sterile cotton swab rolled in the suspension of bacterial and/or fungal cultures. A sterile cork borer of 5mm diameter was used to make wells on inoculated medium.…”
Section: Antimicrobial Activity Using Well Diffusion Methodsmentioning
confidence: 99%